Pemakaian Biodekomposer pada Pertanaman Padi Berumur Genjah di Lahan Sawah pada Musim Kemarau - Meinarti Norma Setiapermas; Ridha Nurlaily (Universitas Muhammadiyah Purworejo, 2021)
Operational steps to increase production are increasing the planted area and increasing productivity. Productivity can be done by, among other things, increasing integrated plants and adding components of biodecomposer technology (M-Dec). Boyolali Regency was chosen as the location for the study of the use of biodecomposers and early maturing rice varieties in the dry season in rainfed rice fields because this location is a center for rice production and has rice fields with very diverse agro-ecosystems. With these diverse agroecosystems, the existing cropping patterns are rice-paddy-paddy, rice-paddy-palawija, rice-palawija-palawija and rice-palawija-bero. The average planting start for the period October 2015 – September 2016 was November (southern Boyolali) and November III-Dec I (northern Boyolali). The location is in Ketitang Village, Nogosari District, Boyolali Regency (northern part) with an agro-ecosystem of problematic irrigated rice fields (water sources from dams or reservoirs). The implementation time is from July to October 2017, it is hoped that the water source will be sufficient. The technology component applied is the variety and dose of fertilizer. The introduction of the technology applied is: a) Inpari 10 and farmer's fertilizer dose, b) Inpari 10 and dose based on PUTS + MDec, c) Inpari 41 and farmer's fertilizer dose, and d) Inpari 41 and fertilizer dose based on PUTS + Mdec. The area for the demonstration plot is about 0.4 ha. The data taken are technical components that are analyzed descriptively. Tile yields on Inpari 10 varieties with recommended fertilizer doses and Mdec were 11.67 tons/ha, Inpari 10 varieties with farmer fertilizer doses of 7.67 tons/ha, Inpari 41 varieties with recommended fertilizer doses and M-Dec 11.33 tons/ha and Inpari 41 varieties with farmer dose of fertilizer is 8.33 tons/ha.